Influence of menopause on inflammatory cytokines during murine and human bone fracture healing - Fischer, Verena; Kalbitz, Miriam; Mueller-Graf, Fabian; Gebhard, Florian; Ignatius, Anita; Liedert, Astrid; Haffner-Luntzer, Melanie (International Journal of Molecular Sciences, 2018)
Postmenopausal females display a chronic inflammatory phenotype with higher levels of circulating pro-inflammatory cytokines. Furthermore, the inflammatory response to injury may be altered under estrogen-deficiency, because it was shown previously that estrogen-deficient mice displayed increased levels of the inflammatory cytokines Midkine (Mdk) and Interleukin-6 (IL-6) in the early fracture hematoma. Because a balanced immune response to fracture is required for successful bone regeneration, this might contribute to the delayed fracture healing frequently observed in osteoporotic, postmenopausal fracture patients. In this study, we aimed to investigate whether further cytokines in addition to Mdk and IL-6 might be affected by estrogen-deficiency after fracture in mice and whether these cytokines are also relevant during human fracture healing. Additionally, we aimed to investigate whether serum from male vs. female fracture patients affects osteogenic differentiation of human mesenchymal stem cells (MSCs). To address these questions, female mice were either sham-operated or ovariectomized (OVX) and subjected to standardized femur osteotomy. A broad panel of pro-and anti-inflammatory cytokines was determined systemically and locally in the fracture hematoma. In a translational approach, serum was collected from healthy controls and patients with an isolated fracture. Mdk and IL-6 serum levels were determined at day 0, day 14 and day 42 after fracture. Subgroup analysis was performed to investigate differences between male and female fracture patients after menopause. In an in vitro approach, human MSCs were cultured with the collected patient serum and osteogenic differentiation was assessed by qPCR and alkaline-phosphatase staining. Our results suggest an important role for the pro-inflammatory cytokines Mdk and IL-6 in the response to fracture in estrogen-deficient mice among all of the measured inflammatory mediators. Notably, both cytokines were also significantly increased in the serum of patients after fracture. However, only Mdk serum levels differed significantly between male and female fracture patients after menopause. MSCs cultivated with serum from female fracture patients displayed significantly reduced osteogenic differentiation, which was attenuated by Mdk-antibody treatment. In conclusion, our study demonstrated increased Mdk levels after fracture in OVX mice and female fracture patients after menopause. Because Mdk is a negative regulator of bone formation, this might contribute to impaired osteoporotic fracture healing.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Bone regeneration; Fracture healing; Inflammation; Menopause; Midkine; Osteoblastogenesis